A catalogue of the geophilomorph centipedes (Chilopoda) from Central and South America including Mexico - Foddai, D.; Pereira, L. A.; Minelli, A. (Amazoniana, 2000)
This paper is an annotated catalogue of the geophilomorph centipedes known from Mexico, Central America.
Keywords: Centopéias